Analisis Penerapan Biaya Kontribusi dan Klaim pada Produk Asuransi jiwa Syariah di PT. Sun Life Financial Syariah Medan - Zainta, Santri Yani; Ulfa, Nadia; Nasution, Rahma Wulan Suci; Syahriza, Rahmi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
PT Sun Life Financial Sharia Plays an active role in developing income contribution (premium) nationally. The purpose of this study is to analyze how application of contribution cost and claims on syariah life insurance products at PT Sun life financial syariah Medan. This study uses aqualitative method to produce descriptive da in the form of observation, interviews, wrtten or oral words about people and the observable behavior. The results of this study indicate that application of contribution cost and claims collected from contribution payments will be divided into several parts namely being used for insurance benefits in the form of funds used as gurantor if there is the riskof participants, as the contribution cost of tabaru which is used for risk insurance funds for syariah insurance participants, and as coverage that will be managed by 2 (two) syariah products in the form of Salam Hijrah Amanah Insurance and Salam Hijrah Investa Insurance. Keywords: Syariah Insurance, Contribution, Claims